PERANCANGAN DAN PENGEMBANGAN PROTOTYPE SISTEM PARKIR - Indah Ayu Septriyaningrum; Dodon T Nugrahadi; Ichsan Ridwan (KLIK- KUMPULAN JURNAL ILMU KOMPUTER, 2016)
Abstract Manual parking systems in mall parking lot services requires a more complex management and development system, not to mention its inefficiency. The information acquired from the parking manager about the the parking space conditions in the field is lacking every day. The purpose of this research is to design and develop a parking system prototype. The development method and system design for this research is the Waterfall method. The results obtained is that this system is able to detect the presence of a vehicle on a designated parking space, with the help of an Intel Galileo Board Gen 2 as the controller, an LDR (Light Dependent Resistor) sensor, and an ultransonic sensor (PING) as an auxiliary. The system is able to display parking activity on a web application, such as empty parking space conditions, occupied parking spaces, time of arrival, parking period, parking space capacity, and also able to display a graphic image of the parking space utilization. It can be concluded that the design and development of the system is successfully implemented.Key Word: Parking system, waterfall, Intel Galileo Board Gen 2, LDR (light dependent resistor) sensor, ultrasonic sensor Abstrak Sistem parkir manual pada pelayanan parkir mall memerlukan pengelolaan dan pengembangan sistem yang lebih rumit dan jauh dari kata efisien. Informasi yang didapatkan pengelola parkir terkait kondisi parkir di lapangan setiap harinya masih kurang. Tujuan dari penelitian ini adalah merancang dan mengembangkan prototype sistem parkir. Metode pengembangan dan perancangan sistem pada penelitian ini adalah metode Waterfall. Hasil yang didapatkan adalah sistem ini dapat mendeteksi keberadaan mobil pada slot parkir yang tersedia dengan bantuan Intel Galileo Board Gen 2 sebagai kontroler, sensor LDR (Light Dependent Resistor) dan sensor ultrasonik (PING) sebagai alat bantu pendeteksi keberadaan mobil. Sistem dapat menampilkan aktifitas parkir pada aplikasi web seperti kondisi lahan parkir kosong, lahan terisi, waktu masuk, waktu keluar, lama parkir dan kapasitas parkir yang tersedia serta grafik pemakaian lahan parkir. Dapat disimpulkan bahwa perancangan dan pengembangan sistem berhasil diimplementasikan.Kata Kunci : Sistem parkir, waterfall, Intel Galileo Board Gen 2,sensor LDR (Light Dependent Resistor), sensor ultrasonik